Inclusion properties of the generalized homogeneous Herz-Morrey spaces - جاسر, علي; محمد علي; حسن بدور (Latakia University Journal -Basic Sciences Series, 2024)
In this paper, we study a problem at functional analysis, it is the inclusion of functional spaces, in the beginning we defined the generalized homogeneous Herz - Morrey space , which is a generalization of the homogeneous Herz- Morrey space, then we studied some of its basic properties, where we proved that it is linear, normed and complete space, then we studied its inclusion properties for different cases of the parameters , then we studied the inclusion between the generalized homogeneous Herz- Morrey space and the weak generalized homogeneous Herz – Morrey space, finally we studied the inclusion between the weak generalized homogeneous Herz – Morrey space.